TECHNOLOGICAL SPEEDS FOR SOIL PREPARATION OF FOREST AREA WITH SPECIAL FORESTRY TILLER - Marinov, Konstantin; Yordanova, Velika (Innovation in Woodworking Industry and Engineering design, 2018)
In this paper are presented the results of an experimental study of the performance of multifunctional forestry tiller FAE 300/S, powered by a self-propelled unit PT-400, for soil preparation for poplar plantations establishment. The machine is tested in different speed regimes while mulching the shrubs, coppice and wood debris from the felling areas. The other observed operation is soil tillage up to 50 cm. The study was conducted in poplar clearings along the Danube River. The purpose is to establish the fuel consumption and the performance of the machine at different milling speed. Based on the results are constructed graphical dependencies, in order to express the relative fuel consumption and operational performance, depending on the operating speed of the machine. At the end is performed an optimization of the process of deep tillage of the soil, using the criteria for minimizing the power consumption. And based on this is defined optimal operating speeds of the examined forestry tiller.